Carotid intima-media thickness and plaque volume changes following 2-year angiotensin II-receptor blockade. The Multicentre Olmesartan atherosclerosis Regression Evaluation (MORE) study - Kl. O. Stumpe; E. Agabiti-Rosei; T. Zielinski; D. Schremmer; J. Scholze; P. Laeis; P. Schwandt; M. Ludwig (Кардиоваскулярная терапия и профилактика, 1970)
Aim. The Multicentre Olmesartan atherosclerosis Regression Evaluation (MORE) study was a double-blind trial in patients with hypertension at increased cardiovascular risk with carotid wall thickening and a defined atherosclerotic plaque that used non-invasive 2- and 3-dimensional (D) ultrasound (US), to compare the effects of a 2-year treatment based on either olmesartan medoxomil or atenolol on common carotid (CC) intima-media thickness (IMT) and plaque volume (PV). Methods. A total of 165 patients (with systolic/diastolic blood pressure 140–180/90–105 mm Hg) were randomized to receive either olmesartan (20–40 mg/day) or atenolol (50–100 mg/day). US was performed at baseline and 28, 52 and 104 weeks. The primary efficacy outcome was the change from baseline (Δ) in CC-IMT assessed by 2D US. Secondary outcomes included ΔPV assessed by 3D US and blood pressure (BP). Results. Olmesartan and atenolol produced comparable significant reductions in CC-IMT; mean ΔIMT (SEM) was −0,090 (0,015) mm for olmesartan and −0,082 (0,014) mm for atenolol. Mean ΔPV was −4,4 (2,3) μl and 0,1 (1,5) μl in the olmesartan and atenolol treated subjects, respectively, without significant between-treatment differences. In the subgroup of patients with baseline PV ≥ median (33,7 μl), significant between-treatment differences existed in ΔPV (p=0,023), because PV regressed significantly with olmesartan (ΔPV: −11,5 (4,4) μl) but not with atenolol (ΔPV: 0,6 (2,5) μl). In these patients BP reductions were comparable. Conclusion. Carotid IMT and BP decreased similarly with olmesartan and atenolol, but only olmesartan reduced the volume of larger atherosclerotic plaques.